Urban Innovation System and the Role of an Open Web-based Platform: The Case of Amsterdam Smart City - Zulfikar Dinar Wahidayat Putra; Wim GM van der Knaap (Journal of Regional and City Planning, 2018)
This study discusses an urban innovation system and the role of digital technology using the Amsterdam Smart City as a case. Based on semi-structured interviews and document analysis, this study reveals that Amsterdam Smart City can be considered an example of a new type of urban innovation system. There are nine actor categories involved with either a one-sided or a bi-directional relationship between them in this innovation system. The actors dynamically interact with each other in different innovation phases based on their interests and resources. Besides, the use of an open web-based platform to connect actors and to exchange information in the innovation system makes the information distributed fairly and transparently among actors. Additionally, more actors can be reached to join the innovation system. There is also no geographical limitation between actors to collaborate and innovate on a specific idea. Therefore, dynamic interactions between actors that are facilitated by an open web-based platform can be a new way of developing an innovation system in urban areas.Keywords. Urban innovation system, smart city, digital technology.Abstrak. Studi ini membahas sistem inovasi perkotaan dan peran teknologi digital, dengan menggunakan Amsterdam Smart City sebagai sebuah kasus. Berdasarkan wawancara semi-terstruktur dan analisis dokumen, penelitian ini mengungkapkan bahwa Amsterdam Smart City dapat dianggap sebagai contoh bentuk baru dari sistem inovasi perkotaan. Ada sembilan kategori aktor yang terlibat dengan hubungan satu-sisi atau dua arah di antara mereka dalam sistem inovasi ini. Para aktor secara dinamis berinteraksi satu sama lain dalam fase inovasi yang berbeda berdasarkan pada minat dan sumber daya mereka. Selain itu, penggunaan platform berbasis web terbuka untuk menghubungkan aktor-aktor dan untuk bertukar informasi dalam sistem inovasi membuat informasi didistribusikan secara adil dan transparan di antara para aktor. Di samping itu, semakin banyak jumlah aktor yang dapat bergabung dengan sistem inovasi ini. Tidak ada batasan geografis di antara para aktor untuk berkolaborasi dan berinovasi pada ide tertentu. Oleh karena itu, interaksi yang dinamis antara para aktor yang difasilitasi oleh platform berbasis web terbuka dapat menjadi cara baru untuk mengembangkan sistem inovasi di wilayah perkotaan.Kata Kunci. Sistem inovasi perkotaan, kota pintar, teknologi digital.